1967
DOI: 10.1063/1.1840448
|View full text |Cite
|
Sign up to set email alerts
|

Physical Properties of Aromatic Hydrocarbons. II. Solidification Behavior of 1,3,5-Tri-α-Naphthylbenzene

Abstract: The kinetics of solidification of 1,3,5-tri-α-naphthylbenzene have been studied from 25° above the glass temperature (69°C) almost to the crystal thermodynamic melting point (199°C). The crystal growth rate has been analyzed using current theories of crystallization and a mechanism for crystal growth has been proposed. It has been demonstrated that mass transport in crystal growth and viscous flow do not have the same temperature dependence. The morphology of the solid phase is discussed. Pertinent parameters … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
99
0

Year Published

1981
1981
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 137 publications
(109 citation statements)
references
References 27 publications
10
99
0
Order By: Relevance
“…This leads to a maximum in the V-∆T relation. This was experimentally observed in a great variety of non-metallic glass-forming systems, such as o-terphenyl [66], tri-α-naphthylbenzene [67], Li 2 O-2SiO 2 [68], and MgO-CaO-2SiO 2 [69]. However, thus far, there is only one work that reports a maximum in the V-∆T relation measured for the Cu 50 Zr 50 glass-forming alloy [32].…”
Section: Dendrite Growth In Undercooled Glass-forming Cu 50 Zr 50 Alloymentioning
confidence: 99%
“…This leads to a maximum in the V-∆T relation. This was experimentally observed in a great variety of non-metallic glass-forming systems, such as o-terphenyl [66], tri-α-naphthylbenzene [67], Li 2 O-2SiO 2 [68], and MgO-CaO-2SiO 2 [69]. However, thus far, there is only one work that reports a maximum in the V-∆T relation measured for the Cu 50 Zr 50 glass-forming alloy [32].…”
Section: Dendrite Growth In Undercooled Glass-forming Cu 50 Zr 50 Alloymentioning
confidence: 99%
“…influence spherulitic growth morphology. Multistage heat treatments on polymeric substances have demonstrated that that both the local growth morphology and growth rate depend on the temperature, but are independent of previous thermal history [1,10,62]. For example, cycling between two temperatures reversibly switches between faceted and spherulitic growth morphologies both in experiment [1,10] and simulation [ Figs.…”
Section: Multi-step Heat Treatmentsmentioning
confidence: 99%
“…While there is no generally accepted theory of spherulite crystallization, a number of phenomenological models and necessary physical conditions for this process have been suggested [1,[8][9][10]22]. The most prevalent conception of their origin is the qualitative model of Keith and Padden [13], in which the presence of static heterogeneities (impurities or molecular defects and mass polydispersity in polymeric materials) lead to a rejection of these components from the growth front to form channels similar to those found in eutectics.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This growth form is most familiar in polymers, where spherulites are the typical crystallization mode 1{6] (although not all polymer solids are crystalline). However, spherulites have a l s o been investigated in materials as dissimilar as elemental selenium 7{9], low molecular-weight systems with polymeric impurities 10], organic materials 11,12], biological molecules 2], mineral aggregates 13{15], and liquid crystals 16{18]. The presence of spherulites in uences the mechanical properties of commercial materials.…”
Section: Introductionmentioning
confidence: 99%